Analisis Kebutuhan Pengembangan Buku Ajar Sejarah Lokal Minangkabau Masa Hindu-Buddha Sampai Penyebaran Islam untuk Meningkatkan Kesadaran Sejarah Siswa SMA - Hakiki, Nurul; Aisiah, Aisiah (Jurusan Sejarah FIS UNP, 2025)
This study was motivated by the low level of students’ historical awareness regarding Minangkabau local history, particularly on the period from the Hindu-Buddhist era to the spread of Islam. Another problem identified is the limited availability of Minangkabau local history textbooks on these periods as learning resources. The purpose of this research is to analyze the need for developing a Minangkabau local history textbook covering the Hindu-Buddhist period and the spread of Islam to foster historical awareness among high school students. This study applied a mixed-methods approach involving 20 tenth-grade students and a history teacher at MAN 1 Bukittinggi. Data were collected through observation, interviews, and surveys using Google Forms, and analyzed both quantitatively and qualitatively. Quantitative results indicate a low level of historical awareness among students, with the average correct answers on knowledge tests ranging only from 5–15%. The survey also revealed that 59% of schools do not yet have Minangkabau local history textbooks on the Hindu-Buddhist period and 54% lack textbooks on the Islamic period. Furthermore, 71% of teachers and 77% of students expressed the need for local history textbooks as learning resources. Qualitative findings from observations and interviews revealed that history learning is still dominated by lecture methods and the use of general textbooks, while teachers have never used specific local history textbooks. The study concludes that the development of a Minangkabau local history textbook is highly needed as a learning resource capable of fostering historical awareness and strengthening students’ identity and appreciation of local culture.